1992
DOI: 10.1002/j.1460-2075.1992.tb05035.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional control in hepatocytes of normal and c14CoS albino deletion mice.

Abstract: The transcription rates of the albumin and alpha‐fetoprotein (alpha FP) genes were reduced to marginally detectable levels in livers of newborn or fetal c14CoS albino deletion mutant mice, which lack the hepatocyte specific developmental regulation (hsdr‐1) locus on chromosome 7 and die shortly after birth. However, steady‐state levels of these two mRNAs in livers of mutant mice were similar to those in normal mice, where these genes are actively transcribed. In c14CoS mice, transcription rates of transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…Sudden apoptotic death of unmasked phenotype of HT1 in mature and unmodified hepatocytes had not been expected (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)16), and these are implications for the pathogenesis and treatment of liver disease in HT1 patients. We suggest that mature and unmodified hepatocytes in those with the FAH defect cannot survive and that hepatocytes in the chronic form of HT1 have to be protected from a likely acute death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sudden apoptotic death of unmasked phenotype of HT1 in mature and unmodified hepatocytes had not been expected (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)16), and these are implications for the pathogenesis and treatment of liver disease in HT1 patients. We suggest that mature and unmodified hepatocytes in those with the FAH defect cannot survive and that hepatocytes in the chronic form of HT1 have to be protected from a likely acute death.…”
Section: Discussionmentioning
confidence: 99%
“…Lethal albino deletion c 14CoS mice and mice with targetdisrupted Fah are models for HT1 (5)(6)(7)(8)(9)(10)(11)(12), but these mice die in the perinatal period, bearing a phenotype different from that seen in HT1 patients (5)(6)(7)(8)(9). Studies on these mice revealed impairment of expression of developmentally regulated genes that are essential for liver functions (6 -11).…”
mentioning
confidence: 99%
“…The locus has been named hsdr-1 (hepatocyte-specific developmental regulation-l; McKnight et al 1989) and alf (albino lethal mutation factor; Ruppert et al 1990), and is referred to here as alf/hsdr-1. Subsequent findings that the genes for several liver-enriched transcription factors are also down-regulated (McKnight et al 1989;Gonzalez et al 1990;Ruppert et al 1990;T6njes et al 1992) have implied a more widespread effect on gene expression than recognized previously. It may be anticipated that a deficit of such factors will impair the induction of hormone-responsive genes.…”
mentioning
confidence: 96%
“…The first might involve reduced expression of transcription factors: The mRNAs for hepatic nuclear factors HNF-1 and HNF-4 are affected most strongly T6njes et al 1992), while HNF-3 and C/EBP show modest reductions (McKnight et al 1989;Ruppert et al 1990;T6njes et al 1992). One or more of these factors might be required for hormone-dependent and/or high-level expression of the TAT and PEPCK genes.…”
Section: The Failure Of Perinatal Activation Of Hormone-dependent Genesmentioning
confidence: 99%
“…A specific deficit of factors in the signal transduction pathways for glucocorticoid and cAMP has not been found, however DeFranco et al 1991). In contrast, the mRNAs for some transcription factors enriched in liver, C/EBP, HNF-1, and HNF-4, are present at reduced levels (McKnight et al 1989;Gonzalez et al 1990;Ruppert et al 1990;T6njes et al 1992).…”
mentioning
confidence: 96%